Pendeteksi Warna Berbasis Arduino pada Aplikasi Deteksi Kematangan Buah-Buahan - Atthariq, Atthariq; Febriansyah, Aan; Salfikar, Inzar (Manutech : Jurnal Teknologi Manufaktur, 2024)
This research leads to the designing of the main color detector Red, Green Blue (RGB) which is applied to the detection of fruit ripeness. The purpose of this research is to help fruit farmers who wants to ensure the maturity condition of the fruits to be harvested. This research uses a scientific approach with the scientific concept of the Closest Pair Point algorithm and the use of the TS3200 color sensor. Closest Pair Point Algorithm is an algorithm that solves the problem of finding the shortest distance between a set of points in a two-dimensional plane. The TCS3200 color sensor is a converter programmed to convert color into a frequency composed of a silicon photodiode configuration and a current-to-frequency converter in a single monolithic CMOS IC. The output of this sensor is a square wave (duty cycle 50%) frequency which is directly proportional to the light intensity (irradiance). The results of the censorship process in the form of RGB numeric values ??will be compared with the original RGB values ??of the maturity provisions of a type of fruit, so that it can provide a resume for determining whether the fruit is ripe or not. The accuracy values ??obtained range between 73,87% - 93,12%.